Relationship between endothelial activation and stress index and all-cause mortality in rheumatoid arthritis patients: a moderating effect of gamma-glutamyl transferase - Chang, Wenjing; Zhao, Zhiming; Ma, Linlin; Lu, Le; Liu, Chunli; Hu, Mengdi; Shang, Wei (Frontiers in Nutrition, 2025)
AimThis study aimed to explore the relationship between endothelial activation and stress index (EASIX) and all-cause mortality in patients with rheumatoid arthritis (RA), and to further examine whether gamma-glutamyl transferase (GGT) influences this association.MethodsWe included 2,543 participants with RA from the National Health and Nutrition Examination Survey (NHANES) in this retrospective cohort study. The study outcome was considered to be all-cause mortality. EASIX and GGT levels were measured at baseline (study enrollment) using laboratory data from NHANES. EASIX was divided into two groups based on its median: ≥0.476 and <0.476, while GGT was divided into two groups based on its median: ≥23 U/L and <23 U/L. EASIX was calculated using the formula, lactate dehydrogenase (LDH, U/L) × creatinine (mg/dL)/platelet count (109/L), based on the baseline laboratory measurements. Weighted multivariate Cox regression models were used to assess the associations between EASIX and GGT with the risk of all-cause mortality. Importantly, a moderated analysis of GGT (moderator) was conducted to examine the relationship between EASIX and all-cause mortality among patients with RA. Additionally, subgroup analysis was performed based on age, duration of arthritis, diabetes, and hypertension.ResultsA total of 867 individuals developed all-cause mortality over a mean follow-up period of 122.86 ± 3.29 months. After fully adjusting for potential confounding factors, higher EASIX (≥0.476) was positively associated with all-cause mortality (hazard ratio [HR] = 1.42; 95% confidence interval [CI]: 1.18–1.73). However, the association between GGT and all-cause mortality was not significant (p > 0.05). Moderated analysis revealed that higher GGT levels strengthened the correlation between EASIX and all-cause mortality among patients with RA (p = 0.013). The association between EASIX and the risk of all-cause mortality varied depending on GGT levels. The subgroup analysis revealed that GGT moderated the relationship between EASIX and all-cause mortality among RA patients aged 60 years or older (p = 0.007), with a history of arthritis lasting more than 5 years (p = 0.040), or diagnosed with diabetes (p = 0.009) or hypertension (p = 0.016). Competing risks analysis accounting for cardiovascular mortality yielded consistent results (subdistribution hazard ratio [sHR] = 1.39; 95% CI: 1.15–1.69), further supporting the primary findings.ConclusionHigh EASIX was positively associated with all-cause mortality in patients with RA, and this association was significantly enhanced by higher GGT levels.